2004
DOI: 10.1038/sj.onc.1207585
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional basis of KRAS oncogene-mediated cellular transformation in ovarian epithelial cells

Abstract: To understand the relationship between oncogenic signaling and the reprogramming of gene expression, we performed transcriptional profiling in rat ovarian surface epithelial cells (ROSE), in which neoplastic transformation is driven by a mutated KRAS oncogene. We identified 4200 genes whose expression was elevated or reduced following permanent KRAS expression. Deregulated KRAS-responsive genes encode transcriptional regulators, signaling effectors, proteases, extracellular matrix and adhesion proteins, transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 76 publications
5
65
1
Order By: Relevance
“…However, blocking the ligand-activated EGF receptor signal transduction pathway by the specific EGF receptor inhibitor, tyrphostin AG1478, and the MEK inhibitor, PD098059, restored the normal level of Lot1 gene expression, indicating that the signaling from the EGF receptor to Lot1 expression is transmitted through MEK-ERK pathway. In agreement with these findings, another study reported that kRAS-induced transformation of ROSE cells downregulates Lot1, which is sensitive to the MEK inhibitor (Tchernitsa et al, 2004). The EGF effect was also confirmed in the human ovarian epithelial cells (Abdollahi et al, 2003).…”
Section: Role Of Growth Factor Signaling Pathwaysupporting
confidence: 76%
“…However, blocking the ligand-activated EGF receptor signal transduction pathway by the specific EGF receptor inhibitor, tyrphostin AG1478, and the MEK inhibitor, PD098059, restored the normal level of Lot1 gene expression, indicating that the signaling from the EGF receptor to Lot1 expression is transmitted through MEK-ERK pathway. In agreement with these findings, another study reported that kRAS-induced transformation of ROSE cells downregulates Lot1, which is sensitive to the MEK inhibitor (Tchernitsa et al, 2004). The EGF effect was also confirmed in the human ovarian epithelial cells (Abdollahi et al, 2003).…”
Section: Role Of Growth Factor Signaling Pathwaysupporting
confidence: 76%
“…c-Fos expression in ovarian carcinoma S Mahner et al our study cannot determine whether the positive prognostic effect of c-Fos is the result of intrinsic differences in malignant potential of the tumours or of differences in chemo-resistance. Findings of previous experimental studies suggested that Fra-1 expression might also have a function in ovarian cancer (Hapke et al, 2003;Tchernitsa et al, 2004). However, our results could not show an impact of Fra-1, Fra-2 and FosB on ovarian cancer progression.…”
Section: Discussioncontrasting
confidence: 56%
“…Taken together with the observation that cells stably transformed with H-RAS or K-RAS oncogenes have increased levels of Fra-1 (43,44), our findings suggest that the MEK-ERK-Fra-1 pathway is a crucial pathway involved in both the initiation and maintenance of transformation by RAS oncogenes. …”
Section: Discussionmentioning
confidence: 73%